Sanfilippo A disease in the fetus. Issue 2 (June 1974) - Harper, P. S.; Laurence, K. M.; Parkes, A.; Wusteman, F. S.; Kresse, H.; Figura, K. Von; Ferguson-Smith, M. A.; Duncan, D. M.; Logan, R. W.; Hall, F.; Whiteman, P.
Abstract : A pregnancy at risk for the Sanfilippo syndrome has been studied in which clear evidence was obtained from the study of amniotic fluid and fetal organs that the fetus was affected. Increased levels of heparan sulphate were found in amniotic fluid and fetal liver, while electronmicroscopy of cultured fetal fibroblasts and fetal liver showed abnormal cytoplasmic inclusions. 35 SO4 uptake studies of cultured fetal cells showed abnormal intracellular accumulation of mucopoly saccharide, while both cultured amniotic cells and fetal skin fibroblasts demonstrated deficiency of heparin sulphamidase, the enzyme responsible for the `A' subtype of the disease. It is suggested that by use of a combination of these methods Sanfilippo A disease can now be diagnosed reliably in utero.